Physicochemical properties and antioxidant potential of honey from Cameroon agroecological zones - Huguette Yangoua; Ruth Edwige Kemadjou Dibacto; Boris Ronald Tonou Tchuente; Emilienne Carine Nyobe; Maxwell Wandji Nguedjo; Tchuenchieu Kamgain Alex Dimitri; Melanie Flore Godam Kamini (Heliyon, 2024)
Cellular respiration produces reactive oxygen species (ROS), which can lead to oxidative stress and significant health issues, including chronic diseases and cancer. Antioxidants play a critical role in neutralizing ROS. This study investigates the physicochemical properties and antioxidant activities of honey sourced from five distinct agroecological zones in Cameroon. Multifloral honey samples (n = 9) were collected from local beekeepers and analyzed for parameters including density, pH, total sugar content, total phenolic content (TPC), flavonoid content (FC), and antioxidant potential (DPPH, FRAP, TAC). The samples ranged in color from light amber to dark amber, with densities between 1.43 and 1.51 g/mL and sugar contents of 70.33 %–83.16 %. pH levels varied from 3.30 to 4.10. Antioxidant analysis revealed phenolic contents ranging from 26.75 to 85.06 mg GAE/100 g and flavonoid contents between 5.22 and 14.47 mg QE/100 g. Significant differences in antioxidant activity were noted, particularly in correlation with color intensity and pH. Honeys with more reddish and greenish hues exhibited better FRAP values, while those with a pH around 4 showed improved DPPH activity. This preliminary study underscores the importance of regional differences in honey quality and its potential health benefits, advocating for further research on the diverse honey types in Cameroon.